Bibliographic survey on the management of sugarcane production/ Levantamento bibliográfico sobre o manejo da produção de cana-deaçúcar - Leandro Antonio de Oliveira; Juliete dos Santos; Maria Ediney Ferreira da Silva (Universidade Estadual de Alagoas, 2016)
This work refers to a literature survey to analyze how to get the academic nature of productions that has as main objective to study the Soil systems in sugar cane production. Thus, this research is constituted as a starting point for carrying out a geographical character study through the selection and evaluation of theses and dissertations, as a major deficiency material returned to this theme in that science. Because of this lack, the works used as a basis for this discussion are mostly carried out by agronomists, therefore, has at its core a very technical language. Thus, these works highlight the relationship between the soil management techniques with the productivity of sugar cane, showing the importance of soil preparation. For, from the type of management combined with pedological potential resulted in a high or low production. To do this, it was necessary a historical approach to culture in Brazil and later in Alagoas in order to check its development and relevance to the region.